1992
DOI: 10.1128/aac.36.10.2139
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin concentration in neutropenic patients with suspected gram-negative sepsis: correlation with clinical outcome and determination of anti-endotoxin core antibodies during therapy with polyclonal immunoglobulin M-enriched immunoglobulins

Abstract: We carried out a study in patients with severe neutropenia from hematologic malignancy and suspected gram-negative sepsis to evaluate the clinical significance of endotoxin concentrations in plasma before and during a therapeutic intervention with a human polyclonal immunoglobulin M (IgM)-enriched immunoglobulin preparation (Pentaglobin; Biotest, Dreieich, Germany). Twenty-one patients with acute leukemia or nonHodgkin's lymphoma entered the study upon the development of clinical signs of gram-negative sepsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 36 publications
(48 reference statements)
8
52
0
3
Order By: Relevance
“…In agreement with the ex-vivo TNFa stimulation assay and the endotoxin levels in sepsis patients (36,37) we identified an almost identical optimum LPS concentration of 500 pg/mL for cytokine production (TNF-a and IL-8) and for morphological shape change and granularity after 3 h incubation in healthy volunteers-except for MPXI. The optimum for fMLP was determined at 44 ng/ mL (10 27 M).…”
Section: Discussionsupporting
confidence: 58%
“…In agreement with the ex-vivo TNFa stimulation assay and the endotoxin levels in sepsis patients (36,37) we identified an almost identical optimum LPS concentration of 500 pg/mL for cytokine production (TNF-a and IL-8) and for morphological shape change and granularity after 3 h incubation in healthy volunteers-except for MPXI. The optimum for fMLP was determined at 44 ng/ mL (10 27 M).…”
Section: Discussionsupporting
confidence: 58%
“…Stehr et al (26) emphasized the benefits of polyclonal IgM-enriched solution by using a rabbit model of bacteremia. Clinical trials showed that IgM-enriched preparations were able to significantly decrease endotoxin levels in plasma (23) and even reduce mortality (22) during the early phase of septic shock. Norrby-Teglund et al (47) showed that IgM-enriched Immune complexes between bacteria and human plasma-derived pIgA, SIgA, mIgA, IgG, IgM, SigM, or anti-Shigella LPS-specific SIgAC5 monoclonal Ab were formed for 1 h as described under "Experimental procedures," and the expression of virulence factors was induced by Congo red.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and clinical studies have underscored the efficacy against various infectious agents of polyclonal IgM-enriched preparations administered by the systemic route (22)(23)(24)(25)(26). Similar to SIgA, SIgM can be seen as a valid candidate immunoglobulin for mucosal application, given its ability to bind antigens with strong avidity, its potential to ensure long term protection (27), its capacity to survive low pH conditions (28), as well as its resistance to proteases (29).…”
mentioning
confidence: 99%
“…Human and equine patients are exquisitely sensitive to the acute effects of endotoxaemia. In both of these species, plasma concentrations of LPS in the picomolar range are associated with severe clinical signs of endotoxaemia, including haematological and metabolic alterations and haemodynamic disturbances leading to multiple organ failure [2][3][4]. It is therefore appropriate to evaluate the effects of LPS experimentally in these species using concentrations of LPS that are likely to be present in endotoxaemic patients.…”
Section: Introductionmentioning
confidence: 99%